Numerical and experimental analyses of a steel “Y” joint with damage - Marko Milošević; Dragoslav Stojić; Srđan Živković; Dragan S. Jovanović (Građevinar, 2023)
Steel damage can significantly impact steel elements’ performance, affecting other structural and non-structural building parts and compromising safety and functioning. Understanding the processes and mechanisms of steel structure damage is crucial for improving its durability. This paper presents numerical and experimental analyses of type “Y” joint behaviour of truss beams in a plane loaded by an axial force, with a special accent on the damage effects. This paper presents the results of numerical and experimental research on the directly welded Y joint of the SHS chord and diagonal members with damage in the joint in the form of a narrow vertical rectangular crack. The deviation of the results obtained by the numerical and experimental procedures was, on average 3 % to 5 %.